Antibiotics and Antimicrobials for Treatment of the Oral Microbiota: Myths and Facts in Research and Clinical Practice - Gaetano Isola (MDPI AG, 2020)
In the dental field, the most common oral diseases include periodontitis, apical periodontitis, abscesses, phlegmons and pulpits, all of which are determined by the same aetiological factor, bacterial infections. For these reasons, it is important to choose the right approach through a target antibiotic therapy against oral bacteria. More specifically, during periodontitis, antibiotics are used, often in association with periodontal debridement, to reduce disease-associated periodontopathogens. However, international guidelines are not unanimous in recommending the use of local and/or systemic antimicrobials to reduce infection by oral bacteria, especially in cases in which there is a danger of spreading systemic infection such as cellulitis, diffuse swelling, and abscesses. The lack of consensus is mainly due to the side effects of antibiotic therapy in dentistry, maybe due to recent scientific evidence regarding the development of bacterial resistance to antibiotics. Therefore, the purpose of this editorial is to analyze the therapeutic effects of antibiotics against the main forms of oral and periodontal diseases, and whether there is a significant clinical benefit, especially in the long term, of antimicrobial therapies in dentistry. The most recent evidence regarding antimicrobial agents will also be discussed.